Misconduct or negligence of employee and losses to employer: recovering losses through salary deduction. - Ali Mohamed, Ashgar Ali (2013)
Majority of the workers are employed to earn a living. Undoubtedly, the wages or salary earned would be used to provide the employed and his family the basic necessities of life such as food, clothing, education, housing, leisure activities and eventually, saving for retirement. Considering that wages earned are the main source of income for most households, the following issues arises and are discussed in this article namely, (i) whether an employer could recover damages or losses from an employee where the latter has been negligent in the performance of his duties or committed misconduct thereby causing the employer to suffer damage or losses, for example, an employee accidentally dropped a tray of dishes or have a customer walkout without paying for the items, among others; and (ii) whether such claim is recoverable from the employee through salary deduction without the employee’s prior consent, given the fact that an employee might be earning a small sum or minimum wages.